Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
2(x - 2)
Step-by-step explanation:
- 4(x + 1) + 6x ← distribute parenthesis by - 4
= - 4x - 4 + 6x ← collect like terms
= 2x - 4 ← factor out 2 from each term
= 2(x - 2)
hello!
=================================================
Let's simplify this expression.
The first step is to use the distributive property, which states:-
[tex]\bigstar{\boxed{a(b+c)}[/tex]
Simplify:-
[tex]\bigstar{\boxed{-4(x+1)}[/tex]
[tex]\longmapsto\sf{-4x-4}[/tex]
Add 6x:-
[tex]\longmapsto\sf{-4x+6x-4}[/tex]
Combine Like Terms:-
[tex]\longmapsto\sf{2x-4}[/tex]
Now, we should write our answer in factored form, so we factor 2 out:-
[tex]\longmapsto\sf{2(x-2)}[/tex]
=============================================
note:-
Hope everything is clear; if you need any clarification/explanation, kindly let me know, and I'll comment and/or edit my answer :)
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.